Bimbingan Perkawinan dalam Tafsȋr Al-Munȋr Karya Wahbah Zuhaili - Siti Novi Nafisah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2022)
This research aims to determine marriage guidance according to contemporary scholar Wahbah Zuhaili in his work Tafsîr al-Munîr. Wahbah Zuhaili (B. 1932) thought that before marriage should pay attention to how to choose a life companion starting from ta'âruf and khitbah, as well as pay attention to the dimension of equality (kafâ'ah) because this can affect the lasting of marriage. The results of this research provide a finding about the meaning of the word sakînah, namely that sakînah or tranquility will only be obtained from the similarity of types and characteristics. This can be contextually meaningful that for the creation of sakînah there needs to be a kafâ'ah or equality and harmony between husband and juga yang bersifat psikologis, wife. The method used in this study is a literature study. The data analysis technique used is descriptive-analytical. The author seeks to accumulate the entire information, after which it is analyzed, as well as presented through a qualitative approach. Furthermore, the review of verses of the Qur'an is reviewed using the thematic interpretation method. The results of this research have similar arguments with the humanistic theory of Abraham Maslow (L. 1908) which explains that human needs are also psychological, not just physiological. According to Maslow, the hierarchy theory of basic human needs at the 3rd level, in the form of the need for ownership and love, namely the need to give and receive affection, is in line with Wahbah Zuhaili's interpretation of the meaning of sakînah mawaddah wa rahmah. Where marital harmony can be realized if the husband and wife both grow mawaddah wa rahmah, namely the attitude of giving and receiving each other, helping each other in facing the problems of living together.